A theoretical analysis to digital marketing adoption by startups - Teixeira, Sérgio (2017)
With the rapid growth in the use of digital platforms for the dissemination and expansion of a company’s business reach, it is vitally important that startup firms are firmly aware of the options when deciding whether to adopt a particular technology because they often have low resource availability, which reduces their margin for error. In order to help these companies to adopt Digital Marketing in a more secure way by knowing the most relevant factors that they can find as concerns the adoption of technologies, this study will analyze the factors that influence the adoption of technology, identifying them initially through the systematic literature review of similar scientific works.